Reference breast phantoms for low-cost microwave imaging - Avşar Aydin, Emine (Array, 2020)
Microwave imaging provides an alternative method for breast cancer screening and the diagnosis of cerebrovascular accidents. Before a surgical operation, the performance of microwave imaging systems should be evaluated on anatomically detailed anthropomorphic phantoms. This paper puts forward the advances in the development of breast phantoms based on 3D printing structures filled with liquid solutions that mimic biological tissues in terms of complex permittivity in a wide microwave frequency band. In this paper; four different experimental scenarios were created, and measurements were performed, and although there are many vector network analyzers on the market, the miniVNA used in this study has been shown to have potential in many biomedical applications such as portable computer-based breast cancer detection studies. We especially investigated the reproducibility of a particular mixture and the ability of some mixes to mimic various breast tissues. Afterwards, the images similar to the experimentally created scenarios were obtained by implementing the inverse radon transform to the obtained data.